Sequences of vesicular stomatitis virus RNA in the region coding for leader RNA, N protein mRNA, and their junction. - Rowlands, D J (1979)
The RNAs extracted from purified preparations of the Indiana and New Jersey serotypes of vesicular stomatitis virus were polyadenylylated in vitro by using polynucleotide phosphorylase and sequence determination was carried out by the dideoxynucleotide method using reverse transcriptase and dT8AC primer. On both virus RNAs a short stretch of adenylic acid residues is present between the regions coding for the leader and N protein mRNAs. Other features of the RNA sequences of the two viruses are compared to each other and to published data.